2006
DOI: 10.1037/0022-006x.74.4.658
|View full text |Cite
|
Sign up to set email alerts
|

Randomized trial of behavioral activation, cognitive therapy, and antidepressant medication in the acute treatment of adults with major depression.

Abstract: Antidepressant medication is considered the current standard for severe depression, and cognitive therapy is the most widely investigated psychosocial treatment for depression. However, not all patients want to take medication, and cognitive therapy has not demonstrated consistent efficacy across trials. Moreover, dismantling designs have suggested that behavioral components may account for the efficacy of cognitive therapy. The present study tested the efficacy of behavioral activation by comparing it with co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

46
1,004
5
44

Year Published

2007
2007
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 1,370 publications
(1,099 citation statements)
references
References 38 publications
46
1,004
5
44
Order By: Relevance
“…Notwithstanding, functional impairment remains a vitally important behavior to target, given that rigorous trials of behavioral activation indicate that even a few months of better functioning significantly improves the long-term course of depression. 22 The primary limitation of this study is its nonexperimental design, specifically that study group assignment was determined by patient preference rather than randomly. As such, we cannot draw definitive conclusions whether intensifying self-management support truly improves mHealth outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Notwithstanding, functional impairment remains a vitally important behavior to target, given that rigorous trials of behavioral activation indicate that even a few months of better functioning significantly improves the long-term course of depression. 22 The primary limitation of this study is its nonexperimental design, specifically that study group assignment was determined by patient preference rather than randomly. As such, we cannot draw definitive conclusions whether intensifying self-management support truly improves mHealth outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence supports this conception, as possessing high levels of dysfunctional attitudes (i.e., negative beliefs about the self) in the absence of a negative life event (indicating entrenched negative core beliefs) is predictive of slower remission in CT (Simons, Gordon, Monroe, & Thase, 1995). Similarly, higher initial depressive severity is also associated with poorer and more delayed remission in CT (Coffman, Martell, Dimidjian, Gallop, & Hollon, 2007;Dimidjian et al, 2006). Rumination has specifically been associated with more severe and longer episodes of depression indicating rumination may also be associated with poorer and delayed remission .…”
Section: Introductionmentioning
confidence: 90%
“…In the general CBT literature, however, it is concluded that the evidence does not show that such change is necessary to achieve improvements in primary outcome measures from CBT. 8,15,45 Focusing on changing cognitive content, such as negative future expectations or critical self-evaluations, may fail in those whose problem is that they already focus on this content too much, such as those with problems with rumination. 24 Also, for some people, approaches that attempt to impose positive self-statements, especially where negative or self-critical thoughts have prevailed, may have the reverse of the intended effect, leaving them feeling more distressed and more self-critical.…”
Section: Model Process and Targets In Cbtmentioning
confidence: 99%